The immunomodulatory activity of secondary metabolites isolated from Streptomyces calvus on human peripheral blood mononuclear cells. Issue 3 (2nd July 2016) - Mahmoudi, Fariba; Baradaran, Behzad; Dehnad, Alireza; Shanehbandi, Dariush; Mohamed Khosroshahi, Leila; Aghapour, Mahyar
Abstract: Background: The natural products derived from micro-organisms are potential candidates for the discovery of novel drugs. Streptomyces bacteria are prolific sources of secondary metabolites with a wide variety of biological activities. Streptomyces calvus ( S. calvus ) is one strain of this genus and may be an appropriate candidate for isolating new compounds. In this study, the immunomodulatory effects of S. calvus secondary metabolites on the expression of various cytokine genes by human peripheral blood mononuclear cells (PBMCs) were evaluated. Methods: A bacterial sample was inoculated in Mueller Hinton Broth and secondary metabolites were extracted. PBMCs were isolated from venous blood and were treated with S. calvus secondary metabolites for 48 h. The cell proliferation was assessed by Methyl tetrazolium bromide (MTT) assay and quantitative real-time polymerase chain reaction (qRT-PCR) assays to survey mRNA expressions of selected pro-inflammatory and inhibitory cytokine genes. Results: Secondary metabolites augmented interleukin-2 and interferon- γ gene expression in PBMCs at low doses and also reduced the levels of immunosuppressive cytokine interleukin-10. In addition, the proliferation of PBMCs substantially increased in response to metabolite treatment in a concentration-dependent manner ( p < 0.001). Conclusion: This in vitro study revealed that the secondary metabolites from S. calvus can successfully stimulate human PBMCs. Therefore, these metabolites have the potential to serve as robust immunomodulators.